2016
DOI: 10.1108/prog-12-2015-0078
|View full text |Cite
|
Sign up to set email alerts
|

Open data framework for sustainable assessment of project-based learning experiences

Abstract: Purpose In a project-based learning experience, the detailed monitoring of the activities in which team members participate can be useful to evaluate their work. However, the project activity produces a large amount of data that can be hardly assessed by a single project supervisor. This poses a scalability issue if the number of users or projects size increases. In this vein, the purpose of this paper is to make the assessment of online learning experiences more sustainable. Design/methodology/approach This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(33 reference statements)
0
0
0
2
Order By: Relevance
“…This systematic review aimed to examine frameworks or tools employed by educators for the identification of student competencies within software engineering courses. A total of twenty studies [39], [40], [49]- [58], [41]- [48], as previously mentioned, were identified. Among the studies reviewed, 55 percent (11 studies) were presented at conferences, while 45 percent (9) found their place in journals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review aimed to examine frameworks or tools employed by educators for the identification of student competencies within software engineering courses. A total of twenty studies [39], [40], [49]- [58], [41]- [48], as previously mentioned, were identified. Among the studies reviewed, 55 percent (11 studies) were presented at conferences, while 45 percent (9) found their place in journals.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of student performance in this competition hinged upon an assessment matrix. Similarly, Traverso-Ribon et al [40] engaged in project-based learning assessment via a webbased technique, also incorporating the use of an assessment matrix.…”
Section: ) Assessment Matrixmentioning
confidence: 99%
“…Este primer número del volumen 17 incluye siete artículos regulares. El primero de ellos lleva por título "Evaluación sostenible de experiencias de aprendizaje basadas en proyectos" y ha sido realizado por Traverso-Ribón et al (2016). En este trabajo se describe una metodología de evaluación orientada al aprendizaje y un framework software de datos abiertos aplicable a la evaluación de proyectos de desarrollo colaborativo.…”
Section: Contenidos Del Númerounclassified
“…Para los estudiantes universitarios, estas tecnologías facilitan el acercamiento a la información y desarrollo de competencias tanto académicas como profesionales, lo cual proporciona una oportunidad para crear nuevos contextos de aprendizaje, más flexibles y personalizados (Traverso-Ribón et al, 2016). Entre estos nuevos contextos destaca especialmente el uso de los videojuegos, ya que de forma habitual se han asociado en exclusiva a entornos de ocio y entretenimiento.…”
Section: Introductionunclassified